From Gambling to Housing: Collective Memory of Cinchona Plantation Residents in West Java, Indonesia - Alissa Wiranova; Budiawati Supangkat; Dede Mulyanto (UIN Sunan Gunung Djati Bandung, 2025)
This study examines the collective memory possessed by local residents in the area of the former Dutch colonial cinchona plantation in Cikembang Village, West Java, which manifests in the form of historical building remnants and oral narratives. Through an ethnohistorical approach, the memory narratives conveyed by residents indicate their attachment to the plantation institution as result of paternalistic relation as a way of labor control. This research demonstrates that, in addition to providing basic necessities and improving moral standards for workers, paternalistic relation were implemented to maintain a continuous supply of plantation labor.